Who's who in the steel consumption in the world: global trends and impact (Quién es quién en el consumo mundial de acero: impactos y tendencias globales) - Bortoni Herrera, Daniel (Facultad de Contaduría Pública y Administración U.A.N.L., 2012)
Abstract. Analyze the behavior of steel production, leads to a necessary research about what the producers can do to get out ahead even when the conditions are not favorable. Coping after a big downturn in the global economy has been an immense task in the entire global economy and mainly in the field of steel. It is important for all countries to stay informed about the situation in the global economy to analyze or surpass the difficulties that may come. What determines the big difference between the leading countries and the rest of the countries regarding steel production? It is important to determine the main differences and identify the key points of improvement; this may help improve the strategy for getting better numbers in order to improve and maintain constant growth of a country and ensure a sustainable development.